Magnetite hybrid photocatalysis: Advance environmental remediation - Bagheri, S. (De Gruyter, 2016)
One of the main public concerns is the aquatic habitat and its corresponding issues because of the incessant contamination of the ecological water systems. In recent years, research attention has been focused on processes that lead to an improved oxidative degradation of organic pollutants. Therefore, semiconductor photocatalysis technology has aroused scientists' interest in environmental remediation. Although several semiconductors have proven to be ideal candidates for the treatment of water pollution, the efficient separation and recycling of this finepowdered photocatalyst is still a scientific problem when applied in practice, including separation process, selectivity, and dispersion. A photocatalyst with magnetic properties allows the use of the technique of magnetic separation, which is one of the most effective and simple methods for removing suspended solids from wastewater without the need for further separation processes. The magnetic photocatalyst allows its use as a suspended material, providing the advantage to have a high surface area for reaction. This review highlights the advantages and disadvantages of current photocatalyst systems. Moreover, it focuses on hybrid magnetic photocatalysts, including metals and nonmetals, metal oxides, carbon-based materials, and ceramics.